IR Sensor Based Obstacle Detection and Avoiding Robot - Arulananth T S, Baskar M, P. Hari babu , R. Divya Sree , R.Sanjana, S.Bhavana (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
An autonomous robot should be made in such a way that it does not require any human control i.e., it should work autonomously. To achieve this task, robots have to avoid obstacles coming in its path. Obstacle detection and avoidance plays major role in robotics. This robot is the first step in building an autonomous industrial robot. This robot uses an IR sensor to detect the objects or obstacles in its path. Then it uses a relay-based switching mechanism to control its motion and to avoid the obstacles. This can be done by a relay and transistor assembly. This is a small attempt to make use of basic electronic components in order to build detection and avoidance mechanisms so that anyone with basic knowledge of electronics can easily understand and implement it.